2016
DOI: 10.3390/rs8020122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sun-Induced Chlorophyll Fluorescence Estimates Obtained from Four Portable Field Spectroradiometers

Abstract: Remote Sensing of Sun-Induced Chlorophyll Fluorescence (SIF) is a research field of growing interest because it offers the potential to quantify actual photosynthesis and to monitor plant status. New satellite missions from the European Space Agency, such as the Earth Explorer 8 FLuorescence EXplorer (FLEX) mission-scheduled to launch in 2022 and aiming at SIF mapping-and from the National Aeronautics and Space Administration (NASA) such as the Orbiting Carbon Observatory-2 (OCO-2) sampling mission launched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…The residual error is lower than a few-tenths of mW m −2 sr −1 nm −1 , and it is probably caused either by slight changes of the reference irradiance spectrum or errors introduced from the 3FLD method. The SIF values retrieved for vegetated targets are higher and fall in the range of values obtained by field spectroscopy measurements reported in the literature [9,[48][49][50]65,72,73]. The obtained results strongly agree with the findings of Rossini et al [73].…”
Section: Radiance Hyuas Reflectancesupporting
confidence: 83%
See 1 more Smart Citation
“…The residual error is lower than a few-tenths of mW m −2 sr −1 nm −1 , and it is probably caused either by slight changes of the reference irradiance spectrum or errors introduced from the 3FLD method. The SIF values retrieved for vegetated targets are higher and fall in the range of values obtained by field spectroscopy measurements reported in the literature [9,[48][49][50]65,72,73]. The obtained results strongly agree with the findings of Rossini et al [73].…”
Section: Radiance Hyuas Reflectancesupporting
confidence: 83%
“…In particular, we computed the far-red fluorescence comparing L inc (λ) and L ref (λ) spectral radiance inside and outside the O 2 -A band, according to the widely-used 3FLD (Fraunhofer Line Depth) approach [8,63]. We limited our analysis to the O 2 -A band because the spectral resolution offered by the USB4000 spectrometer can still provide meaningful results at this broader spectral feature [8,65]; conversely, it is not suitable for retrieving fluorescence at the narrower O 2 -B band. Although the HyUAS measurement approach is very similar to the typical field spectroscopy method, we carried out radiative transfer simulations to assess the impact of atmospheric effects in the limited path length between the target surface and the HyUAS sensor (typically 10 m).…”
Section: Retrieval Of Surface Reflectance and Fluorescencementioning
confidence: 99%
“…However, it is important to note that our ASD FieldSpec ® 4 Standard-Res Spectroradiometer measurements might overestimate true SIF values due to the relative width of the sensor FWHM and that of the O 2 -A absorption line as has been demonstrated by Julitta et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in fluorescence emission values related to measurement techniques, type of instrument and setups are not negligible [14]. Damm et al [15] showed how the accuracy of fluorescence retrievals is affected by the spectral and radiometric resolution of the instruments used.…”
Section: Introductionmentioning
confidence: 99%